Workplace bullying and mental distress - a prospective study of Norwegian employees - Live Bakke Finne; Stein Knardahl; Bjørn Lau (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVES: Using a prospective design, the objective of this study was to determine the relationship between workplace bullying and mental distress. METHODS: Altogether, 1971 Norwegian employees, recruited from 20 organizations, answered questions regarding workplace bullying and mental distress at both baseline and follow-up. Baseline data were gathered between 2004-2006, and follow-up data were gathered between 2006-2009. The time-lag between baseline and follow-up was approximately two years for all the respondents in all the organizations. The factors measured in the study were individual characteristics, mental distress measured with the Hopkins Symptom Checklist (HSCL-10), self-reported workplace bullying measured with a single item from the General Nordic Questionnaire for Psychological and Social Factors at Work (QPSNordic) and job demands and job control assessed by QPSNordic. RESULTS: A multiple linear regression analysis adjusted for mental distress, sex, age, job demands and job control at baseline [β=0.05, 95% confidence interval (95% CI) 0.03-0.17] and a repeated measures ANOVA adjusted for sex and age [F(3,1965)=38.37; partial η^2=0.06] showed that workplace bullying predicted mental distress. Furthermore, a multiple binary logistic regression analysis adjusted for bullying, sex, age, job demands and job control at baseline [odds ratio (OR) 2.30, 95% CI 1.43-3.69] showed that mental distress was a predictor of bullying. CONCLUSIONS: We found support for the notion that self-reported workplace bullying is a predictor of mental distress two years later. Bullying had an independent effect on mental distress after adjusting for job demands and job control. Mental distress was also found to be a predictor of bullying, indicating that the reverse relationship is also important.